Study of glikverin influence on carbohydrate metabolism and histostructure of rats’ pancreatic gland in terms of experimental metabolic syndrome - Chikitkina, O. M.; Kononenko, N. M.; Koshova, O. Y. (Journal of Education, Health and Sport, 2015)
Chikitkina O. M., Kononenko N. M., Koshova O. Y. Study of glikverin influence on carbohydrate metabolism and histostructure of rats’ pancreatic gland in terms of experimental metabolic syndrome = Дослідження впливу глікверину на вуглеводний обмін та гістоструктуру підшлункової залози щурів за умов експериментального метаболічного синдрому. Journal of Education, Health and Sport. 2015;5(11):179-187. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.33701 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A179-187 https://pbn.nauka.gov.pl/works/668523 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 10.11.2015. UDC 615.252.349.7: 616.36-003.826. 616-018 STUDY OF GLIKVERIN INFLUENCE ON CARBOHYDRATE METABOLISM AND HISTOSTRUCTURE OF RATS’ PANCREATIC GLAND IN TERMS OF EXPERIMENTAL METABOLIC SYNDROME ДОСЛІДЖЕННЯ ВПЛИВУ ГЛІКВЕРИНУ НА ВУГЛЕВОДНИЙ ОБМІН ТА ГІСТОСТРУКТУРУ ПІДШЛУНКОВОЇ ЗАЛОЗИ ЩУРІВ ЗА УМОВ ЕКСПЕРИМЕНТАЛЬНОГО МЕТАБОЛІЧНОГО СИНДРОМУ O. M. Chikitkina, N. M. Kononenko, O. Y. Koshova О. М. Чікіткіна, Н. М. Кононенко, О. Ю. Кошова National University of Pharmacy, Kharkiv Національний фармацевтичний університет, м. Харків, Україна Article The article presents the results of the study of Glikverin impact on carbohydrate metabolism and morphological structure of the pancreatic gland in terms of metabolic syndrome in rats induced by high-sucrose diet. It was established that the use of combined agent Glikverin increased tolerance to carbohydrates and improved sensitivity of peripheral tissues to insulin. By expressivity of pharmacological action Glikverin prevailed comparator voglibose and metformin. The results of histological examination of Glikverin showed that it improved morphological condition of β-cells of pancreas, prevented dystrophic and necrobiotic degenerative changes that helped to increase the number of islands, in contrast to the action of the reference drug metformin. This action Glikverin exhibited due to exposure to several pathogenetic chains of metabolic syndrome. The received results justify further pharmacological study Glikverin as a promising agent for treating the manifestations of metabolic syndrome. Key words: metabolic syndrome, glikverin, quercetine, voglibose, metformin, pancreatic gland histostructure. Реферат У статті наведено результати вивчення впливу Глікверину на вуглеводний обмін та морфоструктуру підшлункової залози за умов експериментального метаболічного синдрому у щурів, викликаного високоцукрозною дієтою. Встановлено, що застосування комбінованого засобу Глікверину підвищувало толерантність до вуглеводів та поліпшувало чутливість периферичних тканин до інсуліну. За виразністю фармакологічної дії Глікверин переважав препарати порівняння воглібоз та метформін. За результатами гістологічного дослідження Глікверин, завдяки впливу на декілька патогенетичних ланцюгів метаболічного синдрому МС, покращував морфологічний стан b-клітин підшлункової залози, запобігав дистрофічним та некробіотичним змінам, що сприяло збільшенню кількості острівців, на відміну від дії препарата порівняння метформіну. Отримані результати обґрунтовують подальше фармакологічне вивчення Глікверину як перспективного засобу для лікування проявів метаболічного синдрому. Ключові слова: метаболічний синдром, Глікверин, кверцетин, воглібоз, метформін, гістоструктура підшлункової залози. Реферат ИССЛЕДОВАНИЕ ВЛИЯНИЯ ГЛИКВЕРИНА НА УГЛЕВОДНЫЙ ОБМЕН И ГИСТОСТРУКТУРУ ПОДЖЕЛУДОЧНОЙ ЖЕЛЕЗЫ КРЫС В УСЛОВИЯХ ЭКСПЕРИМЕНТАЛЬНОГО МЕТАБОЛИЧЕСКОГО СИНДРОМА. В статье представлены результаты изучения влияния Гликверина на углеводный обмен и морфоструктуру поджелудочной железы в условиях экспериментального метаболического синдрома у крыс, вызванного высокосахарозной диетой. Установлено, что применение комбинированного средства Гликверина повышало толерантность к углеводам и улучшало чувствительность периферических тканей к инсулину. По выраженности фармакологического действия Гликверин превышал препараты сравнения воглибоз и метформин. По результатам гистологического исследования, Гликверин, благодаря влиянию на несколько патогенетических звеньев метаболического синдрома, улучшал морфологическое состояние b-клеток поджелудочной железы, предотвращал дистрофические и некробиотические изменения, что способствовало увеличению количества островков, в отличие от действия препарата сравнения метформина. Полученные результаты обосновывают дальнейшее фармакологическое изучение Гликверина как перспективного средства для лечения проявлений метаболического синдрома. Ключевые слова: метаболический синдром, Гликверин, кверцетин, воглибоза, метформин, гистоструктура поджелудочной железы.